Genome-Wide Analysis of Transposable Elements and Satellite DNAs in Spinacia Species to Shed Light on Their Roles in Sex Chromosome Evolution - Li, Ning; Li, Xiaoyue; Zhou, Jian; Yu, Li’ang; Li, Shufen; Zhang, Yulan; Qin, Ruiyun; Gao, Wujun; Deng, Chuanliang (Frontiers in Plant Science, 2021)
Sex chromosome evolution has mostly been studied in species with heteromorphic sex chromosomes. The Spinacia genus serves as an ideal model for investigating the evolutionary mechanisms underlying the transition from homomorphic to heteromorphic sex chromosomes. Repetitive sequences play multiple roles in sex chromosome evolution. However, the evolutionary force of repetitive sequences on sex chromosome evolution has not been fully explored in Spinacia species. Here, we identified major repetitive sequence classes in male and female genomes of Spinacia species, and between Spinacia species, and their ancestral relative sugar beet to elucidate the evolutionary processes of sex chromosome evolution using Next-Generation Sequencing data. Comparative analysis suggested that the repeat proportion in the genome of Spinacia species is considerably higher than of sugar beet, especially the Ty3/Gypsy and Ty1/Copia. The long terminal repeat retroelements Angela, Athila and Ogre may be accounted for the higher proportion of repeats in the spinach genome. Comparison of the repeats proportion between female and male genomes of three Spinacia species, indicated that the difference was present in Spinacia tetrandra samples but not in the S. oleracea or S. turkestanica samples. From these results, we speculated that repetitive DNA sequences possibly have a correlation with the formation of sex chromosome and the transition from homomorphic sex chromosomes to heteromorphic sex chromosomes. Three sugar beet-specific satellites were newly identified and confirmed by fluorescence in situ hybridization; eight spinach-specific satellites were also found, six of which were located on the short arm of sex chromosomes. A total of 141 copies of SolSat01-171-s were found in the sex determination region. Thus, the accumulation of satellite DNA on the short arm of chromosome 1 may be involved in the sex chromosome evolution in Spinacia species. Our study provides a fundamental resource for understanding repeat sequences in Spinacia species and their role in sex chromosome evolution.